Oral Health Status of Chinese Children With Autism Spectrum Disorders - Qiao, Yanan; Shi, Han; Wang, Hui; Wang, Mingbang; Chen, Fengshan (Frontiers in Psychiatry, 2020)
Objectives To assess and compare the oral health status of children with and without autism spectrum disorders (ASD) in China. Methods This study recruited 144 children with ASD and 228 unrelated children with typical development (TD) aged 3–16 years from China. Data were collected using parent-reported questionnaires. Oral problems (oral symptoms and habits), oral health measures (oral hygiene practice and dental care experience), and the impact on the child's quality of life (based on a modified version of the Parental-Caregiver Perception Questionnaire) were assessed and compared between the two groups. Results Children with ASD had worse oral health status than children with TD. Oral symptoms were more prevalent in the ASD group, especially halitosis (p < 0.001), food impaction (p < 0.001), and oral lesions (p < 0.001), than the TD group. The rate of damaging oral habits, including mouth breathing (p < 0.001) and object biting (p < 0.05), was also high in the ASD group. Compared with the TD group, more children with ASD did not brush their teeth independently and frequently (p < 0.001), had difficulty accessing dental care (p < 0.01), and reported unpleasant dental experiences (p < 0.001). The presence of ASD was associated with decreased oral health-related quality of life (p < 0.001) in these children and their families. Conclusion Oral problems such as halitosis and bad oral habits are more prevalent among children with ASD. These children also lack oral hygiene practice and dental visits. This situation negatively impacts their quality of life, and must be brought to the attention of their treating dentists.